2021
DOI: 10.3390/ani11020371
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Yeast Products on Modulating Metabolism and Immunity in Cattle and Swine

Abstract: Nutritional supplementation has been used by livestock producers for many years in order to increase animal performance, improve animal health, and reduce negative effects associated with enteric and/or respiratory pathogens. Supplements such as yeast and yeast-based products have broad applications across many livestock production systems, including poultry, aquaculture, cattle, and swine and have been shown to benefit animal production at various stages. These benefits include improvement in milk production,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 79 publications
3
41
1
Order By: Relevance
“…Hence, it indicates that the SC supplementation did not alter the energy metabolism of the high-yield cows. These results were inconsistent with some other studies, who concluded that the live yeast supplementation favorably influenced the metabolic status and might have a liver-protecting effect on the high-yield cows [ 38 , 39 ]. The non-significant results in our study could probably be explained by the fact that the cows used in this experiment were at approximately 70 days into lactation.…”
Section: Discussioncontrasting
confidence: 73%
“…Hence, it indicates that the SC supplementation did not alter the energy metabolism of the high-yield cows. These results were inconsistent with some other studies, who concluded that the live yeast supplementation favorably influenced the metabolic status and might have a liver-protecting effect on the high-yield cows [ 38 , 39 ]. The non-significant results in our study could probably be explained by the fact that the cows used in this experiment were at approximately 70 days into lactation.…”
Section: Discussioncontrasting
confidence: 73%
“…Therefore, dietary interventions aimed at improving gut health and the inflammatory response during HS or nutrient restriction scenarios are of particular interest. Dietary yeast is thought to improve animal performance by maintaining a beneficial intestinal environment, preventing pathogenic bacteria from binding to enterocytes, improving intestinal permeability, and by modulating immune function (Vohra et al, 2016; Che et al., 2017 ; Shurson et al, 2018 , Burdick Sanchez et al, 2021 ). Therefore, we hypothesized that supplementing live yeast would ameliorate some of the adverse effects of HS and nutrient restriction on gut health, which would translate into improved growth performance metrics.…”
Section: Discussionmentioning
confidence: 99%
“…The use of dietary yeast has gained attention as it reportedly has positive effects on both ruminants and monogastrics ( Broadway et al, 2015 ; Shurson, 2018 ; Burdick Sanchez et al, 2021 ). Particularly, dietary live yeast has been shown to improve growth rate, feed efficiency, milk production, and reproductive performance in various species ( Di Giancamillo et al, 2007 ; de Ordanza et al, 2010 ; Nasiri et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The primary reason of this reduction in growth performance is related to a decreased feed intake, due to an altered health status. Furthermore, in this situation, the energy demand can increase by about 10–30% to support the immune system activity, with some estimates even higher at 55% compared to the metabolizable energy needed usually, mainly in the form of glucose [ 22 , 23 , 24 ]. Indeed, the activation of the immune system required at least 0.5 kg of additional glucose in ruminants, with peaks of about 1 kg within a 12 h period [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the activation of the immune system required at least 0.5 kg of additional glucose in ruminants, with peaks of about 1 kg within a 12 h period [ 25 , 26 ]. Consequently, part of the feed-derived energy is shifted toward the activation of the immune system instead of being used for growth [ 23 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%